DEVE (Unit-6) B
DEVE (Unit-6) B
DEVE (Unit-6) B
Vector Integrations
2 ത ҧ 𝑗)ҧ
(𝑥𝑖+𝑦
ത
Now 𝐹. 𝑛ො = (𝑧𝑖 ҧ + 𝑥 𝑗 ҧ − 3𝑦 𝑧𝑘 )( )
4
(𝑥𝑧+𝑥𝑦)
=
4
𝑥(𝑧+𝑦)
=
4
Let us project this surface ABCEA into yz - plane, so
dy.dz dy.dz dy.dz 4
ds = ෝ ҧ => (𝑥𝑖+𝑦 ҧ 𝑗ത) => 𝑥 => 𝑑𝑦𝑑𝑧
n.i .iҧ 𝑥
4 4
In this surface y limits are y = 0,y = 4 and z = 0 to z = 5
4 5 𝑥(𝑧+𝑦) 4
ത
𝐹 𝐴𝐸𝐷𝐵𝐴. 𝑛𝑑𝑠
ො = =𝑦0 (𝑜=𝑧 )( 𝑑𝑦𝑑𝑧)
4 𝑥
4 5
= =𝑦0 𝑧(𝑜=𝑧 + 𝑦) (𝑑𝑦𝑑𝑧)
4 𝑧2
= =𝑦0 ( + 𝑦𝑧)50 (𝑑𝑦)
2
4 25
= =𝑦0 ( + 𝑦(5) ) (𝑑𝑦)
2
4
25 𝑦2 25 42
= 𝑦 + (5) => ( (4) + (5) )
2 2 0 2 2
5
= 50 + (16) => 50 + 40 => 90.
2
Vector Volume Integral:-
Suppose 𝐹ത is a vector function defined over a surface ‘S’
bounded by the volume ‘V’. The Volume Integral of 𝐹ത over ‘V’ can be
ത 𝑑𝑣
denoted and defined as 𝐹 𝑣.
(1) Evaluate 𝑥(𝑉2 + 𝑦 2 + 𝑧 2 )𝑑𝑥𝑑𝑦𝑑𝑧, Where ‘V’ is the volume of the
cube bounded by the co-ordinate plane and the planes 𝑥 = 𝑦 = 𝑧 = 𝑎.
ത 𝑑𝑣 = 𝑥( 2 + 𝑦 2 + 𝑧 2 )𝑑𝑥𝑑𝑦𝑑𝑧
Sol:- Given 𝐹 𝑣. 𝑉
Where ‘V’ is Volume of a cube bounded by the co-ordinate plane and
the planes 𝑥 = 𝑦 = 𝑧 = 𝑎.
Consider,
𝑎 𝑎 𝑎
ത
𝐹 . 𝑑𝑣 = 𝑥( 2 +𝑦 2 + 𝑧 2 )𝑑𝑥𝑑𝑦𝑑𝑧
𝑣 𝑥=0 𝑦=0 𝑧=0
𝑎 𝑎 𝑎
= =𝑥0 =𝑦0 =𝑧0(𝑥 2 +𝑦 2 + 𝑧 2 )𝑑𝑧𝑑𝑦𝑑𝑥
𝑎 𝑎 𝑧3
= =𝑥0 =𝑦0(𝑥 2 𝑧 2
+𝑦 𝑧+
3
)𝑑𝑦𝑑𝑥
𝑎 𝑎 𝑎3
= 𝑥=0 𝑎 𝑦=0(𝑥 2 +𝑦 𝑎+ 2
3
𝑥𝑑𝑦𝑑)
𝑎 𝑦3 𝑎3
= 𝑦𝑎 𝑥=0(𝑥 2 +
3
𝑎+
3
𝑥𝑑)𝑦
𝑎 𝑎4 𝑎4
= 𝑥=0(𝑥 2 𝑎2 +
3
+
3
𝑥𝑑)
𝑥3 𝑎4 𝑎4
(= 𝑎2 + 𝑥+ )𝑥
3 3 3
𝑎3 2 𝑎5 𝑎5
(= 𝑎 + + )
3 3 3
𝑎5 𝑎5 𝑎5 3𝑎5
(= + + >= ) =𝑎5.
3 3 3 3
(2) If Fത = 2xzi ҧ − xj ҧ + 𝑦 2 kത Then Evaluate 𝑉Fത . 𝑑𝑣 Where ‘V’ is the
region bounded by the surface 𝑥 = 0, 𝑥 = 2, 𝑦 = 0, 𝑦 = 6, 𝑧 = 𝑥 2 , 𝑧 = 4.
Sol:- Given, Fത = 2𝑥zi ҧ − 𝑥j ҧ + 𝑦 2 kത
ത 𝑑𝑣 = ( 2𝑥zi ҧ − 𝑥j ҧ + 𝑦 2 kത )𝑑𝑥𝑑𝑦𝑑𝑧
𝐹 .
𝑣
2 6 4
= =𝑥0 =𝑦0 𝑥=𝑧2 (2𝑥zi ҧ − 𝑥 j ҧ + 𝑦 2 kത )𝑑𝑥𝑑𝑦𝑑𝑧
2 6 4
= i ҧ =𝑥0 =𝑦0 𝑥=𝑧2 (2xz )𝑑𝑥𝑑𝑦𝑑𝑧
2 6 4
+j ҧ =𝑥0 =𝑦0 𝑥=𝑧2 (−𝑥)𝑑𝑥𝑑𝑦𝑑𝑧+
2 6 4
ത
+k =𝑥0 =𝑦0 𝑥=𝑧2(𝑦 2 )𝑑𝑥𝑑𝑦𝑑𝑧
4
2 6 𝑧2
= i ҧ =𝑥0 =𝑦0 2𝑥 𝑑𝑥𝑑𝑦
2 𝑥2
2 6 4 2 6 4
ത
+j ҧ =𝑥0 =𝑦0 −𝑥𝑧 𝑥 2 𝑑𝑥𝑑𝑦+k =𝑥0 𝑦2𝑧
=𝑦0 𝑥 2 𝑑𝑥𝑑𝑦
2 6 2𝑥
= i ҧ =𝑥0 =𝑦0 ( (42 − (𝑥 2 )2 )𝑑𝑥𝑑𝑦
2
2 6 2 6
2 ത
+j ҧ =𝑥0 =𝑦0 − 𝑥(4 − 𝑥 )𝑑𝑥𝑑𝑦+k =𝑥0 =𝑦0 𝑦 2 (4
2
− 𝑥 )𝑑𝑥𝑑𝑦
2 6
= i ҧ =𝑥0 =𝑦0 (16𝑥 − −𝑥 5 )𝑑𝑥𝑑𝑦
2 6 2 6
+j ҧ =𝑥0 =𝑦0 (−4𝑥 − 𝑥 3 )𝑑𝑥𝑑𝑦+kത =𝑥0 =𝑦0 (4𝑦 2
− 𝑥 2 𝑦 2 )𝑑𝑥𝑑𝑦
2
= i ҧ =𝑥0 16𝑥𝑦 −𝑥 5 𝑦 60 𝑑𝑥
6
2 2 𝑦3 2𝑦
3
+j ҧ =𝑥0 −4𝑥𝑦 − 𝑥 3 𝑦 60 𝑑𝑥+kത =𝑥0 4 −𝑥 𝑑𝑥
3 3 0
2
= i ҧ =𝑥0 16𝑥(6) −𝑥 5 (6)𝑑𝑥
2 2 63
+j ҧ =𝑥0 (6) (−4𝑥 − 𝑥 )𝑑𝑥+kത
3
=𝑥0 3 (4 − 𝑥 2 ) 𝑑𝑥
2 2 2
𝑥2 𝑥6 𝑥2 𝑥4 63 4 𝑥3
= i(6)
ҧ 16 − +j(6)
ҧ −4 − +kത 𝑥−
2 6 0 2 4 0 3 3 9 0
26 24 63 4 23
= i(6)
ҧ (8(22 ) − )−j(6)(−2(2
ҧ 2
) + ( ))+kത ( (2) − )
6 4 3 3 9
192−64 −32+16 63 24−8
= i(6)
ҧ ( )−j(6)(
ҧ )+kത ( )
6 4 3 9
ത
= 128i ҧ + 24j ҧ + 384k.
(*) Evaluate 𝑉Fത . 𝑑𝑣, Where Fത = 2xzi ҧ − xj ҧ + 𝑦 2 kത Where, ‘V’ is the volume
of the cube bounded by the co-ordinate planes 𝑥 = 𝑦 = 𝑧 = 0,
𝑥 = 𝑦 = 𝑧 = 𝑎.
Green’s Divergent Theorem:-
Statement:-
Suppose ‘R’ is the region bounded by a Closed Jordan Curve
‘C’ and ‘M’,’N’ are any two continious functions of 𝑥 and 𝑦, then
𝜕𝑁 𝜕𝑀
𝑥𝑑𝑀 𝑐ׯ+ 𝑁𝑑𝑦 = (𝑅
𝜕𝑥
−
𝜕𝑦
)𝑑𝑥𝑑𝑦
(1) Verify Green’s Theorem in a plane for
(𝑐3𝑥 2 − 8𝑦 2 )𝑑𝑥 + (4𝑦 − 6𝑥𝑦)𝑑𝑦 Where ‘C’ is the region bounded by
𝑦 = 𝑥 𝑎𝑛𝑑 𝑦 = 𝑥 2 .
Sol:- Given Integral is,
(𝑐3𝑥 2 − 8𝑦 2 )𝑑𝑥 + (4𝑦 − 6𝑥𝑦)𝑑𝑦
Line Integral:-
Given ‘C’ is the boundary of the region
𝑦 = 𝑥 2 𝑎𝑛𝑑 𝑦 = 𝑥
From the firgure we conclude that ‘C’ is made up of two line segments
such as ‘OA’, ‘AO’.
𝐹 𝑐ׯ. 𝑑𝑟ҧ = (𝑐3𝑥 2 − 8𝑦 2 )𝑑𝑥 + (4𝑦 − 6𝑥𝑦)𝑑𝑦
= 𝐴𝑂ׯ+ 𝑂𝐴ׯ----------(1)
Along OA:-
Alone this line 𝑦 = 𝑥 2
𝑑𝑦 = 2𝑥𝑑𝑥
Along this line the two limits of 𝑥 are 𝑥: 0 → 1
1
𝐹 𝑐ׯ. 𝑑 𝑟ҧ = =𝑥0(3𝑥 2 − 8(𝑥 2 )2 )𝑑𝑥 + (4𝑥 2 − 6𝑥(𝑥 2 ))2𝑥𝑑𝑥
1
= =𝑥0(3𝑥 2 − 8𝑥 4 )𝑑𝑥 + (4𝑥 2 − 6𝑥 3 )2𝑥𝑑𝑥
1
= =𝑥0(3𝑥 2 − 8𝑥 4 )𝑑𝑥 + (8𝑥 3 − 12𝑥 4 )𝑑𝑥
1
= =𝑥0(3𝑥 2 + 8𝑥 3 − 20𝑥 4 )𝑑𝑥
1
𝑥3 𝑥4 𝑥5
= 3 +8 − 12 = (1 + 2 − 4) = −1.
3 4 5 0
Along AO:-
Alone this line 𝑦 = 𝑥
1
𝑑𝑦 = 𝑑𝑥
2 𝑥
Along this line the two limits of 𝑥 are 𝑥: 1 → 0
0 1
𝐹 𝑐ׯ. 𝑑 𝑟ҧ = =𝑥1(3𝑥 2 2
− 8( 𝑥) )𝑑𝑥 + (4 𝑥 − 6𝑥 𝑥))(
2 𝑥
𝑑𝑥)
0 𝑥 𝑥 𝑥
= =𝑥1(3𝑥 2 − 8𝑥)𝑑𝑥 + (4
2 𝑥
−6
2 𝑥
)𝑑𝑥
0
= =𝑥1(3𝑥 2 − 8𝑥)𝑑𝑥 + (2 − 3𝑥)𝑑𝑥
0
= =𝑥1(3𝑥 2 − 11𝑥 + 2)𝑑𝑥
0
𝑥3 𝑥2 11 5
= 3 + 11 + 2𝑥 => (1 − + 2) =>
3 2 1 2 2
2 2
𝐹 𝑐ׯ. 𝑑 𝑟ҧ = (𝑐3𝑥 − 8𝑦 )𝑑𝑥 + (4𝑦 − 6𝑥𝑦)𝑑𝑦
= 𝐴𝑂ׯ+ 𝑂𝐴ׯ
5
= −1 +
2
3
= -----------------(A)
2
Double Integral:-
Here 𝑀 = 3𝑥 2 − 8𝑦 2 , 𝑁 = 4𝑦 − 6𝑥𝑦
𝜕𝑀 𝜕𝑁
= −6𝑦 , = −16𝑦
𝜕𝑦 𝜕𝑥
For fixed ‘𝑥’, the two limits of 𝑦 are 𝑦 : 𝑥 2 → 𝑥.
The two limits of 𝑥 are 𝑥 : 0 → 1.
𝜕𝑁 𝜕𝑀 1 𝑥
Consider, (𝑅− )𝑑𝑥𝑑𝑦 = =𝑥0 𝑥=𝑦2 (−6𝑦 + 16𝑦) 𝑑𝑦𝑑𝑥
𝜕𝑥 𝜕𝑦
1 𝑥
= =𝑥0 𝑥=𝑦2 10𝑦 𝑑𝑦𝑑𝑥
𝑥
1 𝑦2
= 10 =𝑥0 𝑑𝑥
2 𝑥2
1 2
= 10 =𝑥0[( 𝑥) −(𝑥 2 )2 ] 𝑑𝑥
1
= 10 =𝑥0[𝑥 − 𝑥 4 ] 𝑑𝑥
1
𝑥2 𝑥5
= 5 −
2 5 0
1 1 3
= 5( − ) => -------------(B)
2 5 2
From equation (A) and (B) we conclude that,
𝜕𝑁 𝜕𝑀
𝑥𝑑𝑀 𝑐ׯ+ 𝑁𝑑𝑦 = 𝑥𝜕 (𝑅− 𝜕𝑦
)𝑑𝑥𝑑𝑦
Hence Green’s theorem is verified.
𝛻𝐹ത = 𝑥 2 + 1
∴ 𝐹 𝑆.
ത 𝑛𝑑𝑠 ത
ො = 𝛻 𝑣. 𝐹𝑑𝑣
𝑎 𝑎 𝑎
= 0 0 0 (𝑥 2 + 1)𝑑𝑥𝑑𝑦𝑑𝑧
𝑎
𝑎 𝑎 𝑥3
= 0 0 +𝑥 𝑑𝑦𝑑𝑧
3 0
𝑎 𝑎 𝑎3
= 0 0 ( + 𝑎)𝑑𝑦𝑑𝑧
3
𝑎
𝑎 𝑎3
= 0 𝑦 + 𝑎𝑦 𝑑𝑧
3 0
𝑎 𝑎3 𝑎 𝑎4
= 0 ( (𝑎) + 𝑎(𝑎))𝑑𝑧 => 0 ( + 𝑎2 )𝑑𝑧
3 3
𝑎
𝑎4 𝑎5
= 𝑧 + 𝑎2 𝑧 => + 𝑎3 -----(B)
3 0 3
ത 𝑛𝑑𝑠
From eq (A) and (B), we conclude that 𝐹 𝑆. ത
ො = 𝛻 𝑣. 𝐹𝑑𝑣
Hence Gauss Theorem is Verified.
(2) Verify Divergence Theorem for
Fത = 4xzi ҧ − y 2 j ҧ + zykത taken over the rectangular
parallepiped x = 0, x = 1, y = 0, y = 1, z = 0, z = 1.
Sol:-Given, Fത = 4xziҧ − y 2 j ҧ + zykത
Given ‘C’ is a rectangle Parallepiped bounded by
x = 0, x = 1, y = 0, y = 1, z = 0, z = 1
From the figure rectangular parallepipe consisting of surface,
Namely OABDO, HGFEH, ODEHO, ABFGA, OHGAO, BDEFB.
ത 𝑛𝑑𝑠
𝐹 𝑆. ො = 𝑂𝐷𝐵𝐴𝑂+ 𝐻𝐸𝐹𝐺𝐻+ 𝑂𝐻𝐸𝐷𝑂+ 𝐴𝐺𝐹𝐵𝐴+ 𝑂𝐴𝐺𝐻𝑂+ 𝐵𝐹𝐸𝐷𝐵-----
(1)
Along OABDO:- This Surface is lying in xy - plane itself
So, 𝑛ො = −𝑘 𝑎𝑛𝑑 𝑧 = 0
Now, 𝐹. ത
ത 𝑛ො = ((4𝑥𝑧)𝑖 ҧ − 𝑦 2 𝑗 ҧ + 𝑦𝑧𝑘)(−
𝑘) => −𝑦𝑧 = 0 => 0
𝑑𝑥.𝑑𝑦
Since this surface is in xy-plane, then 𝑑𝑠 = ො𝑘 ത
𝑛.
𝑑𝑥.𝑑𝑦
𝑑𝑠 = .𝑘
ത
= 𝑑𝑥𝑑𝑦
−𝑘
In this surface 𝑥 ∶ 0 → 1 and 𝑦 ∶ 0 → 1 and z = 0
1 1
ത
𝐹 𝑂𝐷𝐵𝐴𝑂. 𝑛𝑑𝑠
ො = =𝑥0 (𝑜=𝑦0)𝑑𝑦𝑑𝑥 = 0 -----(2)
Along HGFEH:- This Surface is lying in opposite to xy-plane
So, 𝑛ො = 𝑘 𝑎𝑛𝑑 𝑧 = 1
ത 𝑘)
ത 𝑛ො = ((4𝑥𝑧)𝑖 ҧ − 𝑦 2 𝑗 ҧ + 𝑦𝑧𝑘)(
Now, 𝐹. => 𝑦𝑧 = 𝑦(1) = 𝑦
𝑑𝑥.𝑑𝑦
Since this surface is lying in xy-plane, then 𝑑𝑠 = ො𝑘 ത
𝑛.
𝑑𝑥.𝑑𝑦
𝑑𝑠 = .𝑘
ത
= 𝑑𝑥𝑑𝑦
𝑘
In this surface 𝑥: 0 → 1 and y: 0 → 1 and z = 1
1 1
ത
𝐹 𝐻𝐸𝐹𝐺𝐻. 𝑛𝑑𝑠
ො = =𝑥0 𝑥𝑑𝑦𝑑)𝑦(𝑜=𝑦
1
1 𝑦2
= 𝑜=𝑥2 𝑑𝑥
0
1 1 1 1 1
= >= 𝑥𝑑 2 𝑥 0 =>
2 𝑥=𝑜 2
1
ത 𝑛𝑑𝑠
𝐹 𝐻𝐸𝐹𝐺𝐻. ො = -----(3)
2
Along ODEHO:- This Surface is lying in to yz-plane
So, 𝑛ො = −𝑖Ƹ 𝑎𝑛𝑑 𝑥 = 0
Now, 𝐹. ത
ത 𝑛ො = ((4𝑥𝑧)𝑖 ҧ − 𝑦 2 𝑗 ҧ + 𝑦𝑧𝑘)(−𝑖))
Ƹ
= −4𝑥𝑧 => 0
𝑑𝑦.𝑑𝑧
Since this surface is lying in yz - plane, so 𝑑𝑠 = ො ҧ
𝑛.𝑖
𝑑𝑦.𝑑𝑧
𝑑𝑠 = = 𝑑𝑦𝑑𝑧
−𝑖.Ƹ 𝑖ҧ
In this surface 𝑦: 0 → 1 and z: 0 → 1 and 𝑥 = 0
1 1
ത
𝐹 𝑂𝐻𝐸𝐷𝑂. 𝑛𝑑𝑠
ො = =𝑦0 (𝑜=𝑧0)𝑑𝑦𝑑𝑧
=0 -----(4)
Along ABFGA:- This Surface is lying opposite to yz-plane
So, 𝑛ො = 𝑖Ƹ 𝑎𝑛𝑑 𝑥 = 1
Now, 𝐹. ത 𝑖))
ത 𝑛ො = ((4𝑥𝑧)𝑖 ҧ − 𝑦 2 𝑗 ҧ + 𝑦𝑧𝑘)( Ƹ
= 4𝑥𝑧
ത 𝑛ො = 4𝑧
𝐹. 𝑑𝑦.𝑑𝑧
Since this surface is lying in yz - plane, so 𝑑𝑠 = ො ҧ
𝑛.𝑖
𝑑𝑦.𝑑𝑧
𝑑𝑠 = = 𝑑𝑦𝑑𝑧
𝑖.Ƹ 𝑖ҧ
In this surface 𝑦: 0 → 1 and z: 0 → 1 and 𝑥 = 1
1 1
ത
𝐹. 𝑛𝑑𝑠
ො = ( 4𝑧)𝑑𝑧𝑑𝑦
𝑂𝐷𝐸𝐻𝑂 𝑦=0 𝑧=𝑜
1
1 𝑧2 1
= 𝑜=𝑦4 2 𝑑𝑦 =2 𝑦 0 =2 -----(5)
0
Along OHGAO:- This Surface is lying opposite to zx-plane itself
So, 𝑛ො = −𝑗Ƹ 𝑎𝑛𝑑 𝑦 = 0
Now, 𝐹. ത
ത 𝑛ො = ((4𝑥𝑧)𝑖 ҧ − 𝑦 2 𝑗 ҧ + 𝑦𝑧𝑘)(−𝑗))
Ƹ
= 𝑦2
=0
𝑑𝑥.𝑑𝑧
Since this surface is lying in xz - plane, so 𝑑𝑠 = ො ҧ
𝑛.𝑗
𝑑𝑥.𝑑𝑧
𝑑𝑠 = = 𝑑𝑥𝑑𝑧
−𝑗.Ƹ 𝑗ҧ
In this surface 𝑥: 0 → 1 and z: 0 → 1 and y = 0
1 1
ത
𝐹 𝑂𝐴𝐺𝐻𝑂. 𝑛𝑑𝑠
ො = =𝑥0 (𝑜=𝑧0)𝑑𝑥𝑑𝑧 = 0 -----(6)
Along BDEFB:- This Surface is lying opposite to xz-plane
So, 𝑛ො = 𝑗Ƹ 𝑎𝑛𝑑 𝑦 = 1
Now, 𝐹. ത 𝑗))
ത 𝑛ො = ((4𝑥𝑧)𝑖 ҧ − 𝑦 2 𝑗 ҧ + 𝑦𝑧𝑘)( Ƹ
= −𝑦 2
ത 𝑛ො = −1
𝐹.
𝑑𝑥.𝑑𝑧
Since this surface is lying in xz - plane, so 𝑑𝑠 = ො ҧ
𝑛.𝑗
𝑑𝑥.𝑑𝑧
𝑑𝑠 = = 𝑑𝑥𝑑𝑧
𝑗.Ƹ 𝑗ҧ
In this surface 𝑥: 0 → 1 and z: 0 → 1 and y = 1
1 1
ത
𝐹 𝑂𝐻𝐸𝐷𝑂. 𝑛𝑑𝑠
ො = =𝑥0 (𝑜=𝑧−1)𝑑𝑥𝑑𝑧
1 1 1
= −1. )𝑥(𝑜=𝑧10 𝑑𝑧 => −1 𝑧𝑑 𝑜=𝑧 => −1 𝑧𝑑 𝑜=𝑧 => −1 -----(7)
Substitute eq (2) to (7) in eq(1), we get,
1 1 3
ത
𝐹 𝑆. 𝑛𝑑𝑠
ො = 0 + + 0 + 2 + 0 − 1 => 1 + => -----(A)
2 2 2
Volume Integral:-
Given 𝐹ത = (𝑥𝑧)𝑖 ҧ − 𝑦 2 𝑗 ҧ + 𝑦𝑧𝑘ത
𝜕 𝜕 𝜕
𝛻𝐹ത = (𝑖 ҧ +𝑗 ҧ +𝑘ത ത
)((𝑥𝑧)𝑖 ҧ − 𝑦 2 𝑗 ҧ + 𝑦𝑧𝑘)
𝜕𝑥 𝜕𝑦 𝜕𝑧
𝜕 𝜕 2 𝜕
= (𝑥𝑧)+ (𝑦 )+ (𝑦𝑧)
𝜕𝑥 𝜕𝑦 𝜕𝑧
= 4𝑧 − 2𝑦 + 𝑦
𝛻𝐹ത = 4𝑧 − 𝑦
Along this surface 𝑥 = 0, 𝑦 = 0, 𝑧 = 0
𝑥 = 1, 𝑦 = 1, 𝑧 = 1
1 1 1
ത
𝑥𝑑𝑦𝑑𝑧𝑑)𝑦 𝑧=0 (4𝑧 − 𝑦=0 𝑥=0 = 𝑣𝑑𝐹 𝑉 𝛻.
1
1 1 𝑧2
= 0 0 4 𝑧𝑦 − 𝑥𝑑𝑦𝑑
2 0
1 1
= 0 0 𝑥𝑑𝑦𝑑)𝑦 (2 −
1
1 𝑦2
= 0 2𝑦 − 𝑥𝑑
2 0
1 1
= 0 𝑥𝑑) ( 2 −
2
𝑥 1 1 3
= 2𝑥 − => 2 − = )-----(B
2 0 2 2
From eq (A) and (B), we conclude that
ത 𝑛𝑑𝑠
𝐹 𝑆. ത
ො = 𝛻 𝑣. 𝐹𝑑𝑣
Hence Gauss Theorem is Verified.
(3) Apply Divergence Theorem to Evaluate 𝐹 𝑆. ത 𝑁𝑑𝑠,
Where
𝐹ത = 4𝑥𝑖 ҧ − 2𝑦 2 𝑗 ҧ + 𝑧 2 𝑘ത and ‘S’ is the surface bounding the region.
𝑥 2 + 𝑦 2 = 4, 𝑧 = 0 𝑎𝑛𝑑 𝑧 = 3.
Sol:- Given, 𝐹ത = 4𝑥𝑖 ҧ − 2𝑦 2 𝑗 ҧ + 𝑧 2 𝑘ത
𝐷𝑖𝑣 𝐹ത = 𝛻. 𝐹ത
𝜕 𝜕 𝜕
= (𝑖 ҧ + 𝑗 ҧ + 𝑘 )(4𝑥𝑖 ҧ − 2𝑦 2 𝑗 ҧ + 𝑧 2 𝑘) ത
𝜕𝑥 𝜕𝑦 𝜕𝑧
𝜕 𝜕 2 𝜕
= (4𝑥) + (−2𝑦 ) + (𝑧 2 )
𝜕𝑥 𝜕𝑦 𝜕𝑧
𝐷𝑖𝑣 𝐹ത = 𝛻. 𝐹ത = 4 − 4𝑦 + 2𝑧
Along this Surface, 𝑥 = −2, 𝑦 = − 4 − 𝑥 2 , 𝑧 = 0
𝑥 = 2, 𝑦 = 4 − 𝑥 2 , 𝑧 = 3
2 4−𝑥 2 3
ത
𝑣𝑑𝐹 ම 𝛻. = න න 𝑧𝑑𝑦𝑑𝑥𝑑)𝑧න (4 − 4𝑦 + 2
𝑉
𝑥=−2 𝑦=− 4−𝑥 2 𝑧=0
2
= 42𝑥2 =𝑥0 [ 4 − 𝑥 2 ]𝑑𝑥 in 2nd integral is odd function]
𝑥 4 2
−1 𝑥
= 84 4 − 𝑥 2 𝑑𝑥 + sin
2 2 2 0
𝜋
= 84[0 + 2( ) − 0]
2
= 84𝜋
(4) State Gauss Divergence Theorem and use it to
ത
Evaluate 𝑧𝑦( 2 𝑖 + 𝑥𝑧 2 𝑗 ҧ + 2𝑧 2 𝑘)𝑑𝑠. Where ‘S’ is the closed surface
bounded by 𝑥𝑦 - plane and the upper half of the sphere
𝑥 2 + 𝑦 2 + 𝑧 2 = 𝑎2 above this plane.
Sol:- Given 𝐹ത = 𝑦𝑧 2 𝑖 + 𝑥𝑧 2 𝑗 ҧ + 2𝑧 2 𝑘ത
Where,’S’ is the closed surface bounded by xy - place and upper half
of the sphere x 2 + y 2 + z 2 = a2 .
Divergence Theorem states that,
𝐹 𝑆.ത 𝑑𝑠 = 𝛻 . 𝐹𝑑𝑣ത
𝑉
𝜕 𝜕 𝜕
𝐷𝑖𝑣 𝐹ത = 𝛻. 𝐹ത = (𝑖 ҧ + 𝑗ҧ +𝑘 ത
)(𝑦𝑧 2 𝑖 + 𝑥𝑧 2 𝑗 ҧ + 2𝑧 2 𝑘)
𝜕𝑥 𝜕𝑦 𝜕𝑧
𝜕 2 𝜕 2 𝜕
= (yz ) + (xz ) + (2z 2 )
𝜕x 𝜕y 𝜕z
= 4z
S Fത . ds = V 4zdxdydz
In Spherical Polar co-ordinates x = rsin𝜃cos∅
y = rsin𝜃sin∅
z = rcos𝜃 then
dxdydz = r 2 drd𝜃d∅
Substitute above values in equation we get,
a 𝜋 2𝜋
ത
S F. ds = 4 r=0 =𝜃0 =∅0 (rcosθ)(r 2 sin𝜃drd𝜃d∅)
a 𝜋 3 2𝜋
= 4 r=0 =𝜃0 r sinθcos𝜃 (=∅0 d∅)drd𝜃
a 𝜋
= 4 r=0 =𝜃0 r 3 sinθcos𝜃 (2π − 0)drd𝜃
a 3 𝜋
= 4π r=0 r =𝜃0( sin2θ d𝜃)dr
a 3 𝑐𝑜𝑠2𝜃 𝜋
= 4π r=0 r − dr
2 0
−4 a
= π r=0 r 3 (1 − 1)dr
2
a
= −2π r=0 r 3 (0)dr
=0
Stokes Theorem:-
Statement:-
Suppose 𝐹ത is a vector function defined over a surface ‘S’
bounded by a closed curve ‘C’ then,
ത 𝑑𝑟ҧ = 𝐹 ∗ 𝛻 .
𝐹 𝑐ׯ. ത 𝑛𝑑𝑠
ො
𝑆
Where 𝑛ො is a unit normal vector to the surface ‘S’.
(1) Verify Stokes’s Theorem for
𝐹ത = (𝑦 − 𝑧 + 2)𝑖 ҧ + (𝑦𝑧 + 4)𝑗 ҧ − 𝑥𝑧𝑘ത Where ‘S’, is the surface of the cube
bounded by 𝑥 = 0, 𝑦 = 0, 𝑧 = 0, 𝑥 = 2, 𝑦 = 2, 𝑧 = 2 above the 𝑥𝑦 − plane.
Sol:- Given, 𝐹ത = (𝑦 − 𝑧 + 2)𝑖 ҧ + (𝑦𝑧 + 4)𝑗 ҧ − 𝑥𝑧𝑘ത
‘S’ is the surface of the cube bounded by
𝑥 = 0, 𝑦 = 0, 𝑧 = 0, 𝑥 = 2, 𝑦 = 2, 𝑧 = 2
above 𝑥𝑦 − 𝑝𝑙𝑎𝑛𝑒
Line Integral:-
From the firgure we conclude that
𝐹 𝑐ׯ. 𝑑𝑟ҧ = 𝑦(𝑐ׯ− 𝑧 + 2)𝑑𝑥 + (𝑦𝑧 + 4)𝑑𝑦 − 𝑥𝑧𝑑𝑧
𝐹 𝑐ׯ. 𝑑𝑟ҧ = 𝐴𝑂+ 𝐵𝐴+ 𝐷𝐵+ 𝐷0 + 𝐹𝐺+ 𝐸𝐹+ 𝐻𝐸+ 𝐺𝐻----(1)
Where, 𝑧 = 0 => 𝑑𝑧 = 0
𝐹 𝑐ׯ. 𝑑𝑟ҧ = 𝑦(𝑐ׯ+ 2)𝑑𝑥 + 4𝑑𝑦 ----------(2)
Along OA:-
Alone this line 𝑦 = 0, and 𝑥 ∶ 0 → 2
𝑑𝑦 = 0,
𝐹 𝑐ׯ. 𝑑 𝑟ҧ = 𝑦(𝑐ׯ+ 2)𝑑𝑥 + 4𝑑𝑦
(𝐴𝑂0 + 2)𝑑𝑥 + 4(0)
2 2
=𝑥0 2𝑑𝑥 => 2 𝑥 0 => 2 2 − 0 => 4 ---------(3)
Along AB:-
Alone this line 𝑥 = 0, and y ∶ 0 → 2
𝑑𝑥 = 0,
2
=𝑦0(𝑦 + 2)(0) + (4)𝑑𝑦
2 2
=𝑦0 4𝑑𝑦 => 4 𝑦 0 => 4 2 − 0 => 8 ---------(4)
Along BD:-
Alone this line 𝑦 = 2, and 𝑥: 0 → 0
𝑑𝑦 = 0,
0
=𝑥2(2 + 2)𝑑𝑥 + (0)
0 0
=𝑥2 4𝑑𝑥 => 4 𝑥 2 => −8 ---------(5)
Along DO:-
Alone this line 𝑥 = 0, and 𝑦: 2 → 0
𝑑𝑥 = 0,
2 0
=𝑦0 4𝑑𝑦 => 4 𝑦 2 => −8 ---------(6)
Where, 𝑧 = 2 => 𝑑𝑧 = 0
𝐹 𝑐ׯ. 𝑑𝑟ҧ = 𝑦(𝑐ׯ− 𝑧 + 2)𝑑𝑥 + (𝑦𝑧 + 4)𝑑𝑦 − 𝑥𝑧𝑑𝑧
= 𝑦( 𝑐ׯ− 2 + 2)𝑑𝑥 + (𝑦(2) + 4)𝑑𝑦 − 𝑥(2)(0)
= 𝑥𝑑𝑦 𝑐ׯ+ (2𝑦 + 4)𝑑𝑦 --------(7)
Along HG:-
Alone this line 𝑦 = 0, and 𝑥 ∶ 0 → 2
𝑑𝑦 = 0,
𝐹 𝑐ׯ. 𝑑 𝑟ҧ = 𝑥𝑑𝑦 𝑐ׯ+ (2𝑦 + 4)𝑑𝑦
2
=𝑥0(0)𝑑𝑥 + (2(0) + 4) (0) => 0 --------(8)
Along GF:-
Alone this line 𝑥 = 2, and y ∶ 0 → 2
𝑑𝑥 = 0,
2
=𝑦0 𝑦𝑑𝑥 + (2𝑦 + 4)𝑑𝑦
2
=𝑦0 0 + (2𝑦 + 4)𝑑𝑦
2
2 𝑦2
=𝑦0(2𝑦 + 4)𝑑𝑦 => 2
2
+ 4𝑦 =>2 --------(9)
0
Along FE:-
Alone this line 𝑦 = 2, and x ∶ 2 → 0
0 𝑑𝑥 = 0,
=𝑥2 𝑦𝑑𝑥 + (2𝑦 + 4)𝑑𝑦
0
=𝑥2 0𝑑𝑥 + (0)𝑑𝑦 => 0 --------(10)
Along EH:-
Alone this line 𝑥 = 0, and y ∶ 2 → 0
𝑑𝑥 = 0,
2
=𝑦2 𝑦𝑑𝑥 + (2𝑦 + 4)𝑑𝑦
0
=𝑦2 0 + (2𝑦 + 4)𝑑𝑦
0
0 𝑦2
=𝑦2(2𝑦 + 4)𝑑𝑦 => 2
2
+ 4𝑦 => −12 -------(11)
2
Substitute equation 3 to 6 and 8 to 11 we,
𝐹 𝑐ׯ. 𝑑 𝑟ҧ = 4 + 8 − 8 − 8 + 0 + 12 − 12 + 0
= −4. --------------
Surface Integral:-
Given, 𝐹ത = (𝑦 − 𝑧 + 2)𝑖 ҧ + (𝑦𝑧 + 4)𝑗 ҧ − 𝑥𝑧𝑘ഥ
ഥ
𝑖 𝑗ഥ 𝑘ത
𝜕 𝜕 𝜕
𝛻𝑋𝐹ത = 𝜕𝑥 𝜕𝑦 𝜕𝑧
2 2
𝑥𝑦 2𝑥 𝑦𝑧 −3𝑦𝑧 2
𝜕 𝜕 𝜕 𝜕
=> 𝑖[ҧ (𝑦𝑧 + 4) − (𝑦 − 𝑧 + 2)] − 𝑗[ҧ (−𝑥𝑧) − (𝑦 − 𝑧 + 2)] +
𝜕𝑥 𝜕𝑦 𝜕𝑥 𝜕𝑧
𝜕 𝜕
ഥ
𝑘 [ (𝑦𝑧 + 4) − (𝑦 − 𝑧 + 2)]
𝜕𝑥 𝜕𝑦
=> 𝑖[0
ҧ − 𝑦] − 𝑗[−𝑧
ҧ + 1] + 𝑘ഥ [0 − 1]
=> 𝑖(𝑦)
ҧ ҧ − 1) − 𝑘ഥ
+ 𝑗(𝑧
From the figure the surface is lying in ‘xy’ plane, So 𝑛ො = 𝑘ത and
𝑑𝑥.𝑑𝑦 𝑑𝑥.𝑑𝑦
𝑑𝑠 = ො𝑘 ത
= ത .𝑘
ത
= 𝑑𝑥𝑑𝑦
𝑛. 𝑘
ത 𝑛ො = (𝑖(𝑦)
(𝛻𝑋𝐹) ҧ ҧ − 1) − 𝑘ഥ )(𝑘ഥ )
+ 𝑗(𝑧 => −1
2 2 2 2
ത
(𝛻𝑋𝐹)𝑛.
ො 𝑑𝑠 = 0 0 (−1)𝑑𝑥𝑑𝑦 => 0 (−1𝑑𝑥)𝑑𝑦 => 0 −𝑥 02 𝑑𝑦
2 0
=>0 (−2)𝑑𝑦 => −2 𝑦 2 => −2(2) => −4.
(2) State Stokes theorem and applying it to show that
Curl grad∅ = 0
Sol:- Let ‘S’ be the surface enclosed by a simple closed curve’C’
𝑛 )∅𝑑𝑎𝑟𝑔𝑙𝑟𝑢𝑐(𝑆. ො 𝑑𝑠 = 𝑛 )∅𝛻𝑋𝛻(𝑆. ො 𝑑𝑠
= ∅𝛻 𝐶ׯ. 𝑑𝑟ҧ
𝜕∅ 𝜕∅ 𝜕∅
= 𝑖( 𝐶ׯҧ + 𝑗ҧ + 𝑘 ). (𝑑𝑥𝑖 ҧ + 𝑑𝑥 𝑗 ҧ + 𝑑𝑥𝑘ത
ത
𝜕𝑥 𝜕𝑦 𝜕𝑧
𝜕∅ 𝜕∅ 𝜕∅
= ( 𝐶ׯ 𝑑𝑥 + 𝑑𝑦 + 𝑑𝑧)
𝜕𝑥 𝜕𝑦 𝜕𝑧
= ∅𝑑 = (∅)𝑝 (Where P is any point on ‘C’)
∴ 𝑛 )∅𝑑𝑎𝑟𝑔𝑙𝑟𝑢𝑐(𝑆.
ො 𝑑𝑠 = 𝑐𝑢𝑟𝑙. 𝑔𝑟𝑎𝑑∅ = 0